Respostas
respondido por:
0
2 = 3a + b
1 = 2a + b
================
3a + b = 2 (-1)
2a + b = 1
===============
-3a - b = - 2
2a + b = 1
-------------
- a = - 1
a = 1
==============
2.1 + b = 1
b = 1 - 2
b = -1
==============
y = x - 1
1 = 2a + b
================
3a + b = 2 (-1)
2a + b = 1
===============
-3a - b = - 2
2a + b = 1
-------------
- a = - 1
a = 1
==============
2.1 + b = 1
b = 1 - 2
b = -1
==============
y = x - 1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás